Transposable Elements and Their Epigenetic Regulation in Mental Disorders: Current Evidence in the Field - Misiak, Błażej; Ricceri, Laura; Sąsiadek, Maria M. (Frontiers in Genetics, 2019)
Transposable elements (TEs) are highly repetitive DNA sequences in the human genome that are the relics of previous retrotransposition events. Although the majority of TEs are transcriptionally inactive due to acquired mutations or epigenetic processes, around 8% of TEs exert transcriptional activity. It has been found that TEs contribute to somatic mosaicism that accounts for functional specification of various brain cells. Indeed, autonomous retrotransposition of long interspersed element-1 (LINE-1) sequences has been reported in the neural rat progenitor cells from the hippocampus, the human foetal brain and the human embryonic stem cells. Moreover, expression of TEs has been found to regulate immune-inflammatory responses, conditioning immunity against exogenous infections. Therefore, aberrant epigenetic regulation and expression of TEs emerged as a potential mechanism underlying the development of various mental disorders, including autism spectrum disorders (ASD), schizophrenia, bipolar disorder, major depression and Alzheimer’s disease (AD). Consequently, some studies revealed that expression of some sequences of human endogenous retroviruses (HERVs) appears only in a certain group of patients with mental disorders (especially those with schizophrenia, bipolar disorder and ASD) but not in healthy controls. In addition, it has been found that expression of HERVs might be related to subclinical inflammation observed in mental disorders. In this article, we provide an overview of detrimental effects of transposition on the brain development and immune mechanisms with relevance to mental disorders. We show that transposition is not the only mechanism, explaining the way TEs might shape the phenotype of mental disorders. Other mechanisms include the regulation of gene expression and the impact on genomic stability. Next, we review current evidence from studies investigating expression and epigenetic regulation of specific TEs in various mental disorders. Most consistently, these studies indicate altered expression of HERVs and methylation of LINE-1 sequences in patients with ASD, schizophrenia and mood disorders. However, the contribution of TEs to the etiology of AD is poorly documented. Future studies should further investigate the mechanisms linking epigenetic processes, specific TEs and the phenotype of mental disorders to disentangle causal associations.